Deferred Imitation: A 9‐Month Revolution or an Emerging Ability at 6 Months? - Beyer, Sofie A.; Sonne, Trine; Kingo, Osman S.; Krøjgaard, Peter (Infancy)
The ability to engage in deferred imitation is by many scholars considered as one of several social‐cognitive abilities that emerge during what has been coined the "9‐month revolution". Meanwhile, evidence from several studies predominantly using a deferred imitation task with a hand‐held puppet has shown that an emerging ability may be present already from 6 months of age. In the present study, this enigma was addressed by investigating the ability to engage in deferred imitation using five different objects, including the puppet, in 6‐, 8‐, 10‐, and 12‐month‐old infants (N = 200). The results showed that, at group level, infants in all age groups succeeded in deferred imitation tasks with different objects after a 24‐h delay. As expected, older infants imitated more of the demonstrated actions compared to younger infants. These findings add to the understanding of the early development of deferred imitation in infancy and point to important developmental changes during the second part of the first year of life.